To determine if the two numerical expressions \([(110−2)0]3\) and \([(10−4)3]0\) are equivalent, let's simplify each expression step by step.
-
First Expression: \([(110−2)0]3\)
- Calculate \(110 - 2\): \[ 110 - 2 = 108 \]
- The expression now is \([1080]3\). Any number raised to the power of 0 is 1: \[ 1080 = 1 \]
- Raising 1 to any power doesn't change its value: \[ 1^3 = 1 \]
-
Second Expression: \([(10−4)3]0\)
- Calculate \(10 - 4\): \[ 10 - 4 = 6 \]
- Raise 6 to the power of 3: \[ 6^3 = 216 \]
- Now, raise 216 to the power of 0: \[ 216^0 = 1 \]
Now, let's summarize the results:
- \([(110−2)0]3\) simplifies to 1.
- \([(10−4)3]0\) also simplifies to 1.
Since both expressions simplify to 1, the correct answer is:
B) They are equivalent; Both expressions simplify to 1.